Radiographic screening of indigenous South African rodent incisor teeth for the presence of elodontomas - Quintin Norval; Adrian Tordiffe; Gerhard Steenkamp (Discover Animals)
Abstract Elodontomas, benign growths affecting the continuously growing incisor teeth of rodents, are a significant concern in captive populations, often causing severe respiratory distress due to nasal obstruction. This study aimed to investigate the presence of elodontomas in South African rodents to propose a classification system for the anatomical location of maxillary incisor apices, which may influence susceptibility to respiratory issues. Radiographic screening of 376 dry skulls from 63 rodent species housed in the Ditsong National Museum of Natural History's small mammal archives, revealed no evidence of elodontomas. The absence of elodontomas in wild rodents supports the hypothesis that captivity-related factors such as diet, housing, and trauma may contribute to elodontoma development. Rodent species were classified based on the maxillary incisor apex location: Class I (rostral to the first cheek tooth, 80.95%), Class II (between the cheek teeth, 14.29%), and Class III (caudal to the last cheek tooth, 4.76%). The study highlights the importance of additional in-depth research into the incidence of elodontomas, particularly concerning the difference between wild and captive populations. A classification system is proposed that provides a framework for assessing anatomical susceptibility to respiratory distress linked to dental abnormalities, which could offer insights for improving rodent welfare in captive settings.